Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1111/j.1600-079x.2007.00452.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin inhibits lipopolysaccharide‐induced CC chemokine subfamily gene expression in human peripheral blood mononuclear cells in a microarray analysis

Abstract: Melatonin possesses a number of important biologic activities including oncostatic, anti-oxidant, and immunostimulatory actions. This study was designed to assess the effects of melatonin on inflammation-related gene expression in lipopolysaccharide (LPS)-stimulated human peripheral blood mononuclear cells (PBMCs), using CombiMatrix 2K Human Inflammation chip. After pretreatment with melatonin (100 microm) for 4 hr, cells were incubated with LPS (1 microg/mL) for 24 hr. We compared gene expression profiles bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Up-regulation of IL8 has already been reported in pig PBMCs [39,40] and amnion [41] after bacterial infection. In human, stimulation of PBMCs with LPS induces the secretion of CCL2 [42], CXCL3 and CXCL2 [43]. CXCL5 is up-regulated in LPS-challenged bovine mammary epithelial cells [44].…”
Section: Discussionmentioning
confidence: 99%
“…Up-regulation of IL8 has already been reported in pig PBMCs [39,40] and amnion [41] after bacterial infection. In human, stimulation of PBMCs with LPS induces the secretion of CCL2 [42], CXCL3 and CXCL2 [43]. CXCL5 is up-regulated in LPS-challenged bovine mammary epithelial cells [44].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we demonstrated that melatonin inhibited LPS-induced CC chemokine subfamily gene expression in human peripheral blood mononuclear cells using a CombiMatrix 2k Human Inflammation chip [12]. In the present study, we investigated the effect of melatonin on global gene expression in LPS-stimulated RAW 264.7 cells, using a 24K cDNA microarray.…”
Section: Discussionmentioning
confidence: 99%
“…Third, melatonin has an important role in regulating the immune system and therefore inflammation. Via the melatonin receptor 1A (MTNR1A) melatonin reduces the release of interleukin-8 and Tumor necrosis factor (TNF-α) from neutrophils and also markedly reduces the production of CC chemokines by monocytes 21. Melatonin also inhibits activation of nuclear factor kappa-light-chain-enhancer of activated B cells (NFκB) in endothelial cells and reduces leucocyte adhesion to the endothelium, presumably through inhibited expression of Intercellular Adhesion Molecule 1 (ICAM-1) and P-selectin on endothelial cells 22 23.…”
Section: Discussionmentioning
confidence: 99%